1998
DOI: 10.1093/humrep/13.4.822
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged inhibition of presynaptic catecholamine synthesis does not alter leptin secretion in normal-weight men and women

Abstract: Leptin has been called a hormone of reproduction, and seems to link fat and fertility. It has been speculated that the neurotransmitter norepinephrine (NE) (noradrenaline), possibly via the sympathetic nervous system, may represent the afferent signal which modulates leptin release from adipocytes. The purpose of this study was to produce a state of decreased sympathetic output by using the catecholamine synthesis inhibitor alpha-methyl-para-tyrosine (AMPT), in order to study the effect of this compound on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…In resting rodents catecholamines and other β-adrenergic agonists inhibit leptin production and mRNA expression [11,20,29], however, human data are limited and still controversial. Zimmerman et al reported that prolonged inhibition of catecholamine synthesis in normal-weight men and women, did not affect serum leptin levels [46], while in the Pinkney et al study 90 -120 minutes of isoprenaline reduced plasma leptin [33]. In two other investigations plasma catecholamine levels were not related to serum leptin levels in men [24,28] but were significantly correlated to leptin in cycling women [28].…”
Section: Discussionmentioning
confidence: 91%
“…In resting rodents catecholamines and other β-adrenergic agonists inhibit leptin production and mRNA expression [11,20,29], however, human data are limited and still controversial. Zimmerman et al reported that prolonged inhibition of catecholamine synthesis in normal-weight men and women, did not affect serum leptin levels [46], while in the Pinkney et al study 90 -120 minutes of isoprenaline reduced plasma leptin [33]. In two other investigations plasma catecholamine levels were not related to serum leptin levels in men [24,28] but were significantly correlated to leptin in cycling women [28].…”
Section: Discussionmentioning
confidence: 91%
“…84,106 Leptin secretion was not affected by AMPT. 107 No studies were found that investigated the effects on neuroendocrine measures in patient samples.…”
Section: Acute Tryptophan Depletionmentioning
confidence: 99%
“…There is now the ®rst evidence from in vitro and clinical studies for a suppressive effect of catecholamines on leptin secretion in humans (17±23), although some discrepancies remain not fully resolved (24,25). However, to date, it is still unde®ned which speci®c adrenoceptor subtypes are responsible for the inhibition of leptin release from human adipocytes.…”
Section: Introductionmentioning
confidence: 99%